ANALISIS YURIDIS TERHADAP PENCATATAN PERKAWINAN BEDA AGAMA DITINJAU DARI HUKUM PERKAWINAN DI INDONESIA (STUDI PUTUSAN PENGADILAN NEGERI SURABAYA ANTARA RIZAL ADIKARA DAN EKA DEBORA SIDAURUK): Juridical Analysis of Interreligious Marriage Registration in View from Marriage Law in Indonesia (Study of Surabaya District Court Decisions Between Rizal Adikara and Eka Debora Sidauruk - Ashidiqi, Muhammad Hafidz; Setyaningsih (AMICUS CURIAE, 2024)
Interfaith marriage is controversial in society due to the absence of regulation according to the Marriage Law.  Based on Article 2 paragraph (1) of Law No. 1 of 1974, however, in fact, there are still many interfaith marriages in society, one of which is in the decision of the Surabaya District Court.  With the study of the decision no 916/Pdt.p/2022/PN.Sby.  The 2 main issues are whether the determination of interfaith marriages can be registered according to the marriage law in force in Indonesia and whether in court decision No. 916/Pdt.P/2022/PN.Sby.Hakim who has decided to grant permission for interfaith marriages is in accordance with the rules of marriage law in Indonesia.  The research method used is a normative juridical type, with the nature of the research being descriptive and concluding using deductive logic.  Registration of marriages for interfaith marriages cannot be recorded, and the judge's decision is not by the provisions of